Normal sensory and absent cognitive electrophysiological responses in functional visual loss following chemical eye burn - Jiraskova, Nada; Kuba, Miroslav; Kremlacek, Jan; Rozsival, Pavel (Documenta ophthalmologica. Advances in ophthalmology, 2011)
OBJECTIVE: To present a unique case of a 34-year-old patient with unilateral functional visual loss after chemical burn with normal visual evoked potentials (VEPs) and absent cognitive response (P300 wave). METHODS: Visual functions, complete ophthalmic and neurologic examinations including computed tomography of the brain, electrophysiological testing of the visual pathway up to the cognitive brain cortex were evaluated. Data were collected prospectively during 1-year follow-up and compared with data from published case series and a literature review. RESULTS: No abnormalities were found that could account for such a rapid monocular loss of vision with exception of absence of the P300 wave in the affected eye during cognitive tasks. Vision slowly improved during 1 year without any treatment. CONCLUSIONS: Functional vision loss is a diagnosis of exclusion. In the event of reduced vision in the context of a normal ocular health examination, all other pathology must be ruled out before the diagnosis of functional visual loss is established. Complex visual electrophysiological testing is the preferred tool for objective examination of such disorders.
Keywords: Evoked Potentials, Visual; testy zrakového pole; poruchy zraku; zraková pole; Sensory Thresholds; Male; zrakové evokované potenciály; zraková ostrost; kognitivní poruchy; chemické popálení; Visual Fields; Electroretinography; Adult; Retina; Prospective Studies; dospělí; mužské pohlaví; Visual Acuity; popálení oka; lidé; Vision Disorders; Humans; Cognition Disorders; Burns, Chemical; senzorické prahy; Eye Burns; retina; elektroretinografie; Visual Field Tests; prospektivní studie